Nonlinear Cointegration, Misspecification and Bimodality - Marcelo C. Medeiros; Eduardo Mendes; Les Oxley (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
We show that the asymptotic distribution of the ordinary least squares estimator in a cointegration regression may be bimodal. A simple case arises when the intercept is erroneously omitted from the estimated model or in nonlinear-in-variables models with endogenous regressors. In the latter case, a solution is to use an instrumental variable estimator. The core results in this paper also generalises to more complicated nonlinear models involving integrated time series.
Keywords: 330; Cointegration; nonlinearity; bimodality; misspecification; instrumental variables; asymptotic theory.